Por uma geohistória cartográfica: epistemologia das relações entre espaço, tempo e mapa, e seu contexto a partir do Renascimento - Bruno Zambianchi Rey (Confins)
The reflections’ purpose is to explore the theoretical and philosophical relations between geography and history (space and time) in their paths as modern sciences, mainly through an analysis of french geographical traditions, amongst which are the spatial notions of vidalian and braudelian thought, and the critical responses to them. This work acknowledges the need for a renewal that incorporates in geohistoric methods an attention to the role that maps and cartographic language play in the historical production of relative spaces. To demonstrate these dynamics, the writing approaches the contexts of geographic knowledge in the Renaissance, including cosmography and chorography, to broaden notions of historical spatialities and their forms of abstraction, and to give cartography a main function in understanding geographies of past times.